Evaluation of the impact of pharmaceutical trainings and tools on the proper use of medicines in pediatrics - Charles, F.; Castet-Nicolas, A.; Amouroux, C.; Moreau, J.; Werner, O.; Morin, D.; Berland, P.; Fila, M.; de Barry, G. (Frontiers in Pharmacology, 2023)
Introduction After 6 years of medication errors’ (ME) collection and analysis in a paediatric unit of a French University Hospital, the number of MEs was no longer decreasing. We then decided to set up pharmaceutical trainings and tools and evaluate their impact on the occurrence of ME. Materials and methods This monocentric prospective study was carried out in the form of audits of prescriptions, preparations, and administrations before and after intervention (A1 and A2). After the analysis of A1 results, a feedback was given to the teams, some tools for the proper use of medication (PUM) were distributed, and A2 was conducted. Finally, A1 and A2 results were compared. Results Each audit included 202 observations. 120 MEs were identified during A1 and 54 for A2 (p<0.0001). Observation rate with at least 1 ME decreased from 39.11% to 21.29% (p<0.0001) and no observation had more than 2 MEs during A2 in contrast to A1 (n=12). Human factors were responsible for the majority of MEs. The audit feedback allowed professionals to feel concerned about ME. The PUM tools received an average satisfaction rating of 9/10. The staff had never participated in this type of training and all felt it was useful to PUM. Conclusions This study showed a significant impact of pharmaceutical training and tools on paediatric PUM. Clinical pharmaceutic actions allowed us to reach our objectives and satisfied all the staff. They must therefore be continued to limit human factors’ impact and thus contribute to the safety of drug management in paediatrics.